2022
DOI: 10.1021/acsaem.2c01479
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructing Oxygen Vacancies in the Bulk and Nickel Oxyhydroxide Overlayer to Promote the Hematite Photoanode for Photoelectrochemical Water Oxidation

Abstract: Surface engineering, as an efficient strategy, can improve the photoelectrochemical water splitting (PEC-WS) performance for converting inexhaustible sunlight into clean hydrogen fuel. Oxyhydroxides and p–n heterojunctions have been demonstrated as efficient catalysts for the water oxidation reaction. In this work, to address the drawbacks of poor conductivity and sluggish oxidation kinetics of hematite, we introduce a p-type NiOOH overlayer as a surface catalyst onto n-type Sn-doping hematite (Sn@α-Fe2O3) pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 67 publications
(111 reference statements)
0
19
0
Order By: Relevance
“…The selective equivalent circuits (EC) for the charge transfer process of ZnO‐based photoanode under illumination are shown in Figure 4a, where R S represent the series resistance (including the solution resistance and the contact resistance), R CT and C SC represents the charge transport resistance at the ZnO‐electrolyte interface and the space charge capacitance, respectively. The fitting parameters are summarized in Table S2, and the FTO/TiO 2 /ZnO/NiO photoanode shows the smallest transport resistance, which is consistent with the optimal PEC‐WS performance [55] . The Mott‐Schottky spectra are employed to analyse the effect of TiO 2 and NiO on the charge density ( N D ) of ZnO photoanode (Figure 4b), and the N D can be calculated according to the slope [56] .…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…The selective equivalent circuits (EC) for the charge transfer process of ZnO‐based photoanode under illumination are shown in Figure 4a, where R S represent the series resistance (including the solution resistance and the contact resistance), R CT and C SC represents the charge transport resistance at the ZnO‐electrolyte interface and the space charge capacitance, respectively. The fitting parameters are summarized in Table S2, and the FTO/TiO 2 /ZnO/NiO photoanode shows the smallest transport resistance, which is consistent with the optimal PEC‐WS performance [55] . The Mott‐Schottky spectra are employed to analyse the effect of TiO 2 and NiO on the charge density ( N D ) of ZnO photoanode (Figure 4b), and the N D can be calculated according to the slope [56] .…”
Section: Resultsmentioning
confidence: 61%
“…The fitting parameters are summarized in Table S2, and the FTO/TiO 2 /ZnO/NiO photoanode shows the smallest transport resistance, which is consistent with the optimal PEC-WS performance. [55] The Mott-Schottky spectra are employed to analyse the effect of TiO 2 and NiO on the charge density (N D ) of ZnO photoanode (Figure 4b), and the N D can be calculated according to the slope. [56] The positive slope implies that the ZnO photoanode belongs to n-type semiconductor.…”
Section: Chemistryselectmentioning
confidence: 99%
“…The fitting peaks for Co 2+ and Co 3+ species implied the co-existence of both Co 2+ and Co 3+ in TiO 2 /CoS x /NiS and TiO 2 /CdS/CoS x /NiS. Moreover, in the Ni 2p spectra (Figure b), the binding energy of Ni 2p 3/2 and Ni 2p 1/2 could be divided into two peaks, suggesting the successful decoration of CoNi-MOF or NiS . As demonstrated in Figure c,d, after the ion exchange with Cd 2+ , the peaks of Cd 3d 3/2 and Cd 3d 5/2 appeared while the peaks of S 2p 1/2 and S 2p 3/2 negatively shifted, indicating the successful construction of TiO 2 /CdS/CoS x /NiS and strong interaction between CoS x /NiS and CdS.…”
Section: Resultsmentioning
confidence: 80%
“…Compared with the original Sn@α-Fe 2 O 3 photoanode, enhanced photocurrent and decreased onset potential could be achieved after reconstruction of oxygen vacancies, owing to the improved charge separation. 78…”
Section: The Structure Optimization Of Oer Catalysts In Pec Water Oxi...mentioning
confidence: 99%
“…Compared with the original Sn@a-Fe 2 O 3 photoanode, enhanced photocurrent and decreased onset potential could be achieved aer reconstruction of oxygen vacancies, owing to the improved charge separation. 78 Recently, other strategies such as heteroatom incorporation, in situ activation and precursor regulation have also been demonstrated to construct oxygen defects in OER catalysts for further promoting the PEC water splitting activity. For instance, Wang et al reported a two-step photo-assisted electrodeposition and subsequent calcination process for incorporating Fe into CoO x to form FeCoO x with abundant oxygen defects, which drastically increased the photocurrent density of the BiVO 4 photoanode to 4.82 mA cm −2 at 1.23 V RHE (Fig.…”
Section: Oxygen Defect Constructionmentioning
confidence: 99%